2010
DOI: 10.1186/1471-2202-11-130
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PrPC monoclonal antibody infusion as a novel treatment for cognitive deficits in an alzheimer's disease model mouse

Abstract: BackgroundAlzheimer's Disease (AD) is the most common of the conformational neurodegenerative disorders characterized by the conversion of a normal biological protein into a β-sheet-rich pathological isoform. In AD the normal soluble Aβ (sAβ) forms oligomers and fibrils which assemble into neuritic plaques. The most toxic form of Aβ is thought to be oligomeric. A recent study reveals the cellular prion protein, PrPC, to be a receptor for Aβ oligomers. Aβ oligomers suppress LTP signal in murine hippocampal slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
137
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 43 publications
(74 reference statements)
4
137
0
Order By: Relevance
“…20 In animal experiments it was possible to counteract detrimental effects of Aβ and rescue parts of cognitive function by applying antibodies directed against PrP C . 19,[21][22][23] Considering all these findings, it stands to reason that further research on this topic is necessary, since PrP C might be useful as an AD biomarker as well as a potential therapeutic target. 24 Put into a clinical perspective, Meyne et al were able to demonstrate levels of CSF PrP C to be decreased in various neurodegenerative diseases including AD.…”
Section: Methodsmentioning
confidence: 99%
“…20 In animal experiments it was possible to counteract detrimental effects of Aβ and rescue parts of cognitive function by applying antibodies directed against PrP C . 19,[21][22][23] Considering all these findings, it stands to reason that further research on this topic is necessary, since PrP C might be useful as an AD biomarker as well as a potential therapeutic target. 24 Put into a clinical perspective, Meyne et al were able to demonstrate levels of CSF PrP C to be decreased in various neurodegenerative diseases including AD.…”
Section: Methodsmentioning
confidence: 99%
“…7 Treatment of aged APP swe / PS1DE9 mice with anti-PrP C antibodies allows a recovery of synaptic markers in the dentate gyrus of the hippocampus, a brain region associated with learning and memory. 18 Neuroinflammation occurs in TBI and many other neurodegenerative disorders. Proinflammatory cytokines, including tumor necrosis factor a (TNFa) and interleukin (IL)-1b, are increased in mild TBI and modulate deficits in motor coordination.…”
Section: Prpmentioning
confidence: 99%
“…Interaction between A␤o and PrP C is essential for development of an array of AD features, including activation of certain signaling cascades, synaptotoxicity, inhibition of long term potentiation, memory impairment, and decreased survival in mice (25,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). However, it was also observed that A␤o can induce AD-like phenotypes independently of PrP C in J20 mice (44) and in some in vitro studies (23,24,45).…”
mentioning
confidence: 99%